Transformasi Digital dan Dampaknya terhadap Kemampuan Berpikir Analisis Peserta Didik - Kusmardiningsih, Wahju Tri (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
Digital transformation in education has yielded significant impacts on the analytical thinking abilities of learners. This article explores these changes, emphasizing various aspects. First, it delves into the challenges arising alongside digital transformation, such as accessibility gaps, the technology learning curve, and concerns related to data security. Furthermore, the article discusses opportunities that can be leveraged to enhance learners' analytical thinking, including project-based learning, data analysis competitions, and the use of digital technology. The positive impact of digital transformation on learners' analytical thinking skills is highlighted in this abstract. Factors such as access to information resources, interactive and adaptive learning, and the use of data analysis technology are explained as major contributors. Additionally, game-based learning, customized evaluation and feedback, and empowering teachers through technology adaptation are highlighted in the context of enhancing analytical thinking skills. This article also details the importance of continually adapting to technological changes in education, discussing aspects such as real-world relevance, learner engagement, personalized learning, and online education. These points culminate with an emphasis on preparing learners to face future challenges, improving the efficiency and effectiveness of learning processes, and lifelong learning through the development of technological skills. In essence, the article illustrates how essential digital transformation is in laying a robust foundation for learners' analytical thinking abilities in the modern era.